Factors associated with pain-related functional interference in people with chronic low back pain enrolled in a physical exercise programme: the role of pain, sleep, and quality of life - Marta Moreno-Ligero; Alejandro Salazar; Inmaculada Failde; Rogelio del Pino; M. Carmen Coronilla; Jose A. Moral-Munoz (Medical Journals Sweden, 2024)
Objective: To identify the factors associated with the pain-related functional interference level in people with chronic low back pain. Design: Cross-sectional. Subjects/Patients: Chronic low back pain patients. Methods: Sociodemographic data, pain intensity, pain-related functional interference, physical functioning and fitness, sleep quality, anxiety and depression, social support, and health-related quality of life were recorded. Descriptive and bivariate analyses were performed. A linear regression model was carried out to identify the factors associated with the pain-related functional interference level. Results: 99 participants were involved (mean age: 54.37 SD: 12.44; women: 67.7%). 37.4%, 27.3%, and 35.4% were classified into low, moderate, and high pain-related functional interference level groups, respectively. Higher pain-related functional interference was associated with higher pain intensity (β: 0.724; p = 0.026), worse sleep quality (β: 0.077; p = 0.012), worse quality of life (physical (β: -0.539; p < 0.001) and mental (β: -0.289; p < 0.001), and lower consumption of weak opioids (β: -3.408; p = 0.037). Conclusion: Beyond the pain experience and intensity among people with chronic low back pain, several biopsychosocial factors associated with this condition has been identified. Furthermore, higher pain intensity, worse sleep quality, worse quality of life, and weak opioids' consumption have been related to the pain-related functional interference of this population.